Deviation of Body Weight Estimation using Lambourne Formula Against Aceh Bull’s Actual Body Weight - Hasan Muhammad; Lubis Utari D.M.; Meutia Nellita; Hambal Muhammad; Gani Fadli A.; Masyitha Dian (E3S Web of Conferences, 2020)
This study aims to determine the percentage of body weight deviation of Aceh bull using the Lambourne formula and compared to the actual weight of Aceh bull. The sample used in this study was 50 Aceh bull aged 2-2.5 years in BPTU-HPT Indrapuri Aceh. The parameters observed were Body Length (BL), Chest Circumference (CC), and Body Weight (BW). BL measurement procedure was conducted by measuring the distance between the lateral humeral tuberculum to the ischiadium tuberculum using a measuring stick. CC was measured by encircling the chest cavity which is behind the shoulder bone joint (os scapula) using measuring tape. BW measurement procedure was carried out in two ways, first with digital livestock scales and second with Lambourne formula. The percentage of body weight deviation of Aceh bull using Lambourne formula to the actual’s Aceh bull body weight was 3.41% with regression equation was Y = -350.30 + 2.27x1 + 2.06x2.